Morphophysiological and production responses of peanut (Arachis hypogaea L.) ‘Takar 2’ to organic, biological, and NPK fertilizers - Arjuna Puji Darmasandi; Iskandar Lubis; Heni Purnamawati (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
Peanuts (Arachis hypogaea L.) is the second most important type of legume after soybeans in Indonesia. Fertilizers were given in either organic or inorganic forms. However, the continuous use of chemical fertilizers was found to have negative impacts on the environment and the microorganisms in the soil. Therefore, organic and biological fertilizers were recommended because they had positive effects on both the environment and the soil’s microorganisms. Some of the bacteria that were beneficial for plant growth were Pseudomonas sp. and Azotobacter sp. This study aimed to analyze the use of organic fertilizers, biological fertilizers, and NPK combinations on the growth and yield of peanut plants of the Takar 2 variety. The study was conducted from March to June 2024, located at the Leuwikopo Experimental Station of IPB, Bogor, Indonesia. The experiment used a randomized complete block design (RCBD) with two factors and three replications. The factors are NPK fertilizer doses (100% and 50% recommended dose) and types of organic + biological fertilizer (control, Azotobacter sp., Pseudomonas sp., humate, and a combination of humate and biological fertilizer). Observations were made on 5 sample plants per treatment. The characteristics observed were plant morphology, physiological characteristics, and plant production. The results of the study showed that the application of 100% NPK fertilizer at the recommended dose, in combination with Pseudomonas sp., Azotobacter sp., and humate, had a significant effect on various morphological, physiological, and production-related plant variables. This study shows the potential for a combination of NPK and organic biological fertilizers to increase the growth and production of peanuts. Keywords: Azotobacter sp; humate; morphology; physiology; Pseudomonas sp